STAGES AND PSYCHOLOGY OF PRESCHOOL-AGE CHILDREN - Ergasheva Sarvinoz Ulug’bek qizi (International Journal of Innovations in Engineering Research and Technology, 2024)
This article will focus on changes in early childhood, the influence of the social environment on the child, and the natural states observed at this time. The growth of thinking, emotions, and will in preschool children is highlighted.